RONGENG DANCE AS AN ENTERTAINMENT SPECIAL IN THE DYNAMIC OF SIMPANG TONANG COMMUNITY: TARI RONGGENG SEBAGAI TONTONAN HIBURAN DALAM DINAMIKA MASYARAKAT SIMPANG TONANG - Indrayuda Indrayuda; Ranti Lestari (LLDIKTI Wilayah X, 2023)
This article aims to analyze and to reveal the development and changes in the Ronggeng dance in the dynamic socio-cultural life of the people of Simpang Tonang. The dynamic of the people's lives at Simpang Tonang is one of the indicators of changes in today's Ronggeng dance performances. The novelty of this article is to examine the issue of changes in the Ronggeng dance due to the dynamic of changes in the social life of the people of Simpang Tonang. This research was conducted qualitatively with the explanatory method. The selection of informants in this study was carried out by purposive sampling, so that the selection of informants was based on the objectives and objectives of the research study. The researcher acted as the key instrument, conducted interviews, and directed observation of the object of research that was assisted by equipment such as audio-visual and guided by interview and observation guides. Data were collected through involved observation and structured and unstructured interviews. Data were analyzed based on the steps taken by Miles and Huberman namely data collection, data reduction, data presentation and data verification and data analysis conclusions. It is found that the factors that influence the development and change of the Ronggeng dance are sociological factors, aesthetic factors, value factors. Sociological factors can be seen in the use of the Ronggeng dance which is used in society, changes occur due to social influences such as lifestyle, status, and roles of individuals and groups. Aesthetic factors, the development of people's tastes causes changes in the form and model of Ronggeng dance performances such as at weddings. The value factor in which the existence of the Ronggeng dance is not only judged by its use as entertainment, but has become part of the value of status and social stratification for the people of Simpang Tonang.